(3GdQjGVjGJ (B:s (3GdeaGgje GdYGeI,GdeYGOdGJ hGdeJQGLMGJ,GdOhGd GdYOOjI,GdOhGd cKjQ GdMOhO,MSGH GdeKdKGJ (B/s - (3OgHj, fhQIs ((3YeGf(B: s (3OGQ UaGA(B, s, 2005)
(3JVef gPG GdcJGH NeSI aUhd TedJ Cge ehGVjY GdQjGVjGJ GdJMdjdjI cGdJGdj (B: (3GdebOeI(B-(3GdHGH GdChd (B: (3GdeaGgje GdYGeI (B: (3GdeLehYGJ (B: (3eLehYGJ GdCYOGO (B: (3cKjQGJ GdMOhO (B: (3hMjOGJ GdMOhO (B: (3LPhQ cKjQ MOhO (B: (3GdLPQ GdHSjW (B: (3GdLPQ GdeVGYa(B-(3GdHGH GdKGfj (B: (3GdeYGOdGJ hGdeJQGLMGJ ef GdOQLI GdKGfjI (B: (3GdTcd GdfehPLj dcKjQ MOhO ef GdOQLI GdKGfjI (B: (3GdeYGOdGJ ef GdOQLI GdKGfjI (B: (3GdeJQGLMGJ ef GdOQLI GdKGfjI (B: (3ebGQfg YOO HLPQj cKjQ MOhO ef GdOQLI GdKGfjI (B: (3GdeYGOdGJ GdUMjMI (B: (3GdeJQGLMGJ GdUMjMI (B: (3GdeYGOdGJ hGdeJQGLYGJ GdeVGYa GdJQHjY(B-(3GdHGH GdKGdK (B: (3YehejGJ GdOhGd GdYOOjI (B: (3GdOhGd GdYOOjI (B((3GdGbJQGfGJ(B) : (3GdYdjGJ Ydi GdOhGd (B: (3GJLGg JZjQ OGdI Ydi eLGd (B: (3fSHI JRGjO OGdI (B: (3GdOhGd GdRhLjI (B: (3GdOhGd GdaQOjI (B: (3GdOhGd GdOhQjI (B: (3GdfgGjGJ (B: (3fgGjGJ eLehY OGdJjf (B: (3fgGjI LOGA OGdJjf (B: (3fgGjI GdLPQ GdJQHjYi dOGdI(B-(3GdHGH GdQGHY (B: (3GdOhGd cKjQ GdMOhO (B: (3eNWW OQGSI OGdI (B: (3GdOhGd GdfGWbI (B: (3GdaQY GddGfgGFj (B: (3GdOhGd GdeKdKjI (B: (3OQGSI GdOhGd GdOGFQjI(B-(3GdHGH GdNGeS (B: (3eQGLYI aj MSGH GdeKdKGJ (B: (3GdOGFQI GdeKdKjI (B: (3LjH JeGe hLjH YOO Mbjbi (B: (3Xd hXd JeGe YOO Mbjbi (B: (3OSGJjQ GdJMhjd (B: (3OSGJjQ GdLeYs
(3HjHdjhZQGajG U(B.222s
Keywords: (3GdOhGd GdYOOjIs; (3GdeJQGLeGJs; (3GdeYGOdGJs; (3MSGH GdeKdKGJs